JAEPL, Vol. 17, Winter 2011-2012 - Joona Smitherman Trapp; Brad Peters (Journal of the Assembly for Expanded Perspectives on Learning, 2011)
Essays Cristina Bruns - Immersion, Transformation, and the Literature Class Anne DiPardo - My Kanawha Kelly A. Concannon Mannise - Who Cares? Exploring Student Perspectives on Care Ethics Kym Buchanan & Perry Cook - Playing the Believing Game with Dr. Seuss and Reluctant Learners in Science Elizabeth Woodworth - Being the Unbook, Being the Change: The Transformative Power of Open Sources W. Keith Duffy - Suffering and Teaching Writing Helen Collins Stitler - Perfect Nikki Holland, Iris Shepard, Christian Z. Goering, & David A. Jolliffe - We Were the Teachers, Not the Observers: Transforming Preparation through Placements in a Creative, After-School Program S. Rebecca Leigh - Re-Seeing Story through Portal Writing Nicole Warwick - "Poetry Is Not a Luxury": Why We Should Include Poetry In the Writing Classroom Out of the Box Colette Morrow - Notes from Teaching at the Ends of the Earth Book Reviews Judy Halden-Sullivan - Evolution and Criticism Julie J. Nichols - Boyd, Brian. On the Origin of Stories: Evolution, Cognition, and Fiction. Cambridge: Belknap Press of the Harvard University Press, 2009. Julie J. Nichols - Zunshine, Lisa. Why We Read Fiction: Theory of Mind and the Novel. Columbus: Ohio State University Press, 2006 Mary Pettice - Dutton, Denis. The Art Instinct: Beauty, Pleasure, and Human Evolution. 2nd edition. New York: Bloomsbury Press, 2010. Print. Connecting Helen Walker - Teaching/Seeing Jesus Jan Buley - The Realization S. Rebecca Leigh - Celebrating Ways of Learning Christopher M. Bache - The Opening Question Bette B. Bauer - Teaching as a Spiritual Practice Rachel Forrester - Appalachia Finally in the Spring Laurence Musgrove - Syllabus